drainage system, infiltration well , retention pond, rainwater harvesting, clean water , rainwater tank. - Bunaputra, Joventa
The design of Surakarta Great Mosque Bulding Design in the field of water resources consist of drainage system and rainwater utilization. The drainage system is designed with the eco-drainage concept. This concept makes rainwater that falls into the specified area flowed into the reservoir for reuse. The drainage system is designed with rational method by using rainfall with 2-year return period normal probability. In addition to drainage channels, the components that will be designed in the drainage system are infiltration wells to reduce the runoff of the mosque’s region. Rainwater harvesting design is a concept in utilizing rainwater in the mosque area. The need for clean water in the mosque building will be fulfilled by rainwater which the amount of availability is calculated through 80% mainstay discharge. The rain water will be stored in rainwater tanks and retention ponds. The design will be carried out using the Ministry of Public Works' Drainage Channel System making guide. Rainfall data used is obtained through Global Weather online website with a span of 10 years. The results of this design are in the form of drainage schemes, drainage section dimensions, infiltration well dimensions, retention pool dimensions, and rainwater tank dimensions with roof pipe size.